Consensus guidelines for dosing of amoxicillin-clavulanate in melioidosis. - Cheng, A; Chierakul, W; Chaowagul, W; Chetchotisakd, P; Limmathurotsakul, D; Dance, D; Peacock, S; Currie, B (2008)
Melioidosis is an infectious disease endemic to northern Australia and Southeast Asia. In response to clinical confusion regarding the appropriate dose of amoxicillin-clavulanate, we have developed guidelines for the appropriate dosing of this second-line agent. For eradication therapy for melioidosis, we recommend 20/5 mg/kg orally, three times daily.